Theoretical bases of synthesis of quasi-orthogonal systems of complex signals - Gorbenko, I.D.; Zamula, A.A. (Radiotekhnika, 2020)
Functioning of a number of modern infocommunication systems (ICS) is carried out under external and internal influences, caused, on the one hand, by natural interference, interference from other radio systems operating at close frequencies or in a common part of the frequency range, on the other hand, intentional interference created by counteraction stations with the aim of electronic suppression of existing systems. Possible strategies of the counter station are as follows: determining the content of messages when legal subscribers use cryptographic data protection algorithms; falsification of messages; violation of data integrity; staging of various types of interference, etc. Therefore, more stringent requirements are imposed on the ICS, especially for critical purposes, to ensure the effectiveness of their functioning: reliability and speed of information transfer, survivability, noise immunity, information security. In such conditions, the presence and use of protected ICS is of particular importance. Under the security systems one should understand, first of all, their ability to provide the necessary indicators for noise immunity, information, energy and structural secrecy, information transfer speed, frequency and energy efficiency. The need for the use of secure systems makes researchers take a fresh look at both the modes of operation of secure radio channels and the aspects of formation and use of complex signals – physical data carriers for such systems. In this paper, based on the study of the algebraic structure of systems of non-linear parametric irregularities, the problems of synthesis of a number of classes of quasi-optimal uniform, non-uniform, complex discrete signals with specified correlation, ensemble and structural properties, including such signal systems that have the properties “blur" by correlation properties. This property means that an increase or decrease in the duration of a discrete sequence does not change the correlation properties of the signal, on the basis of which the signal is synthesized. It is shown that the use of many of the indicated signal systems in modern information and communication systems will improve such indicators of the functioning of such systems as noise immunity, operational secrecy, information security, noise immunity of signal reception.